The Decorative Wooden Ceilings of Nasrid Granada and the Alhambra - Mc Sweeney, Anna (My University, 2024)
This article examines the role of Nasrid Granada in the development and spread of decorative wooden ceilings or artesonados in the late medieval and early modern periods. It argues that it was in the intensive building projects of the Nasrids in the fourteenth century that the techniques of carpintería de lo blanco were perfected, and that highly decorative geometric designs in ceilings became popular in royal palace contexts. Through four case studies from Granada and the Alhambra, it explores the making and meaning of these ceilings and examines their role in the display of royal power and authority
IN_PRESS
Keywords: Architecture History; Cultural Heritage; Cultural History; Decorative Arts; Furniture; History of Islam; Islamic art; Medieval Europe; Museum Studies; Visual Arts; al Andalus